Everything you love will burn : inside the rebirth of white nationalism in America - Tenold, Vegas (Nation Books, 2018)
Reveals how white supremacist and nationalist groups rose in influence to achieve political support at the highest levels of government, examining the transformation of once-small groups into threatening mainstream organizations.